2009
DOI: 10.1177/089686080902902s25
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Referral is Early Referral

Abstract: The number of patients receiving renal replacement therapy in the United Kingdom is rapidly rising. Chronic kidney disease (CKD) is a worldwide public health problem with significant comorbidity and mortality. Several organizational guidelines have been developed in an attempt to identify when appropriate referral to nephrology services should occur; however, many of these guidelines provide conflicting recommendations on referral. Recent surveys suggest that more than 30% of patients with CKD are referred lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…This led to questionable PD and HD comparison in this group. [34][35][36] Moreover, we described previously that pulmonary fluid overload was the cause of dialysis emergency start in 80% of the cases, regardless of CHF comorbidity status. 36 The validation study confirmed the potential misclassification bias: two-thirds of patients misclassified as having CHF had begun dialysis in emergency.…”
Section: Discussionmentioning
confidence: 99%
“…This led to questionable PD and HD comparison in this group. [34][35][36] Moreover, we described previously that pulmonary fluid overload was the cause of dialysis emergency start in 80% of the cases, regardless of CHF comorbidity status. 36 The validation study confirmed the potential misclassification bias: two-thirds of patients misclassified as having CHF had begun dialysis in emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is both a national and international public health priority because of its association with significant morbidity and mortality (1). It has been previously demonstrated that patients with CKD have a better outcome when they have access to specialist nephrology services early in the course of their disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with representatives from 60 Spanish hospitals have revealed that ∼35% of hospitals have multidisciplinary monographic ACKD clinics, 40% have conventional monographic ACKD clinics and 25% lack these clinics. In the United Kingdom, very few units had a full complement of the recommended multidisciplinary renal team [ 32 ]. Lack of programmed RRT initiation .…”
Section: Current Status and Pitfalls In Pre-dialysis Carementioning
confidence: 99%